Non-replicating Vaccinia Virus TianTan Strain (NTV) Translation Arrest of Viral Late Protein Synthesis Associated With Anti-viral Host Factor SAMD9 - Zhao, Ying; Zhao, Li; Huang, Panpan; Ren, Jiao; Zhang, Peng; Tian, Houwen; Tan, Wenjie (Frontiers in Cellular and Infection Microbiology, 2020)
NTV is a highly attenuated virus that was created by genetically deleting 26 genes related to host range and virulence from TianTan strain. Since NTV is highly attenuated, it has been used widely as an optimizing viral vector. In this study, we explored the biological characteristics in vitro and the host restriction mechanism of NTV. Most cell lines do not support sufficient dissemination and replication of NTV, and in non-permissive cell line HeLa, the replication block of NTV occurred at the translation stage of viral late protein expression. Lack of PKR activity was not sufficient to rescue expression of viral late proteins and replication, even though the phosphorylation level of eIF2α increased in NTV-infected HeLa cells. Moreover, the translation inhibition of NTV in HeLa cells was dependent upon a SAMD9 signaling pathway, as demonstrated by silencing SAMD9 expression with siRNA and observing the colocalization of SAMD9 and AVGs. Reinserting C7L or K1L into NTV rescued the late viral protein expression and replication of NTV in HeLa cells. Among the genes deleted in NTV, C7L or/and K1L gene was mainly responsible for its replication defect. Protein C7 interacted with SAMD9, which antagonized the antiviral response of SAMD9 to ensure viral protein translation and replication of NTV in non-permissive cell lines. Our finding will serve as a baseline for modification of NTV in future application.